Strategy for cultural inclusion in new product development processes: A New Zealand study - Sanjay Mathrani; Sara Diaa Eldin Ibrahim (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Cultural inclusion generates a positive impact by socially increasing pride for individuals or economically increasing a country's global capital. Currently, in New Zealand (NZ), not many strategies exist that ensure inclusion of culture in new products introduced locally and globally. Further, cultural inclusion in products appears highly represented in the tourist markets, but not so much in the domestic markets. This paper examines the current NZ strategies for cultural inclusion in product development of different sized companies that supply locally and globally through three case studies and compares the findings with theoretical models used in other regions. Findings elaborate that NZ lacks in documented standardized strategies when it comes to cultural inclusion. A positive impact of having such a strategy is perceived by participating companies with a culture for open innovation to ensure they are following a process approach that can help include cultural aspects appropriately. Creating a unique position for the brand globally, increasing global capital and deeper connectivity, and increasing the understanding of culture were some key benefits identified. However, a few steps in the new product development process were found largely lacking in NZ firms, such as communication with cultural representatives and leaders. A cultural inclusion model is developed based on the study findings to include an open innovation culture that can help NZ companies be more inclusive in their design and establish a unique NZ market for generating positive impacts.
Keywords: 650; cultural inclusion; new product development; open innovation; product design; strategy